PEMETAAN STATUS HARA K, Ca, Mg TANAH PADA KEBUN KELAPA SAWIT (Elaeis guineensis Jacq) DI PERKEBUNAN RAKYAT KECAMATAN HUTABAYU RAJA KABUPATEN SIMALUNGUN - Star Marudur Pangaribuan; Supriadi Supriadi; Sarifuddi Sarifuddi (Jurnal Agroekoteknologi, 2013)
Mapping survey in order to classify, analyze and soil mapping by grouping at soils which have thesame characteristics a certain mapping unit. The objective of this research is to mapping of K, Ca,and Mg of soils at people Palm oil estate of Hutabayu Raja, Simalungun District. This researchwas begun in Juni 2011 until Februari 2012. Soil nutrient data obtained through free sampling gridmethod. Mapping and classification using Geographic Information System with criteria nutrientstatus of BPPT (1983) and BPP Medan (2005). The result of research indicate that mediumPotassium,very low Calcium and low Magnesium (0,3 Ha), medium Potassium, very low Calciumand very low Magnesium (204 Ha), high Potassium, very low Calcium and low Magnesium (5 Ha)and high Potassium, very low Calcium and very low Magnesium ( 90 Ha).Keywords : mapping survey, potassium, calcium, magnesium